THE CRISIS AND RACISM ARE BOTH SPREADING: REACTIONS FROM BELOW - Teresa Sordé Martí; Panayota Gounari; Donaldo Macedo (Ediciones Universidad de Salamanca, 2009)
Amidst the economic crisis, racist and xenophobic discourses are increasingly present in the public sphere. Actions and measures that criminalize immigrants and cultural minorities are reinforcing previously existing inequalities. In this article, it is argued that grassroots actions are the ones are fighting against those positions which use the economic crisis to justify the advancement of discrimination towards those sectors who are more socially excluded.